Examination of social media usage in teacher-parent communication: Whatsapp example - (:unkn) unknown (Sakarya University, 2016)
The purpose in this study schools under the parent-teacher created with the purpose of ensuring the communication Whatsapp shared in the conversation history of Whatsapp in terms of the type of the media preferred, and investigate them separately about teacher and parents sharing. In addition, the viewpoints of the teachers on the subject have also been examined. In the study, which was designed as a case study, the example of Whatsapp was dealt with as a social media tools used in teacher-parent communication. The study was conducted with a guidance teacher who had instant messaging groups with the parents and who worked at a private primary school (4th Graders) in the city of Istanbul, since it was easily available. In examining the messages that were shared in the Whatsapp group in terms of the media type and the titles of the subjects that was preferred, the Whatsapp history was used; and in determining the viewpoints of the teacher on the Whatsapp group, semi-structured interview method was used. According to the findings of the study, the teaches considers the instant messaging group as a healthy social media platform for the purpose of establishing communication with the parents; however, is insufficient in informing the parents about educational and pedagogical instructions for them. It was observed that the group members were not sensitive about the private messages and about the messaging hours. © The Turkish Online Journal of Educational Technology.